Experimental Study on the Influence of Aging on Mechanical Properties of Geogrids and Bearing Capacity of Reinforced Sand Cushion - Hui Yuan; Xiaohong Bai; Hehui Zhao; Jingren Wang (Advances in Civil Engineering)
Geogrids are widely used in foundation engineering for reinforcing foundations due to their light weight, high strength, and excellent performance. In this study, two kinds of polypropylene biaxial geogrids were used, and indoor thermal oxygen and photooxygen aging tests were carried out. The residual mechanical stability of the exposed materials was determined by tensile testing. The results of both accelerated test methods are discussed and compared in detail. After aging of the geogrid, the trend of tensile strength and fracture elongation change with aging time is obtained. The gray prediction model was used to predict the variation in the retention rate of tensile strength in the geogrid with photooxygen aging time. Model tests of cushions were carried out in a large geogroove to compare the load bearing characteristics of pure sand and the unaged and aged geogrid-reinforced sand cushions. The results show that ultraviolet radiation illuminance plays a decisive role in the aging degree of the polypropylene geogrid. The influence of photooxygen aging on the tensile strength and fracture elongation of a polypropylene biaxial geogrid is greater than that of thermal oxygen aging. Different types of polypropylene biaxial geogrids with photooxygen aging showed different retention rates of tensile strength, and the aging resistance of the geogrid with higher tensile strength was significantly higher than that of the geogrid with lower tensile strength. The tensile strength of the geogrid has an effect on the bearing capacity of reinforced sand cushions. Under proper elongation, the bearing capacity of the reinforced sand cushion is clearly improved compared with that of the unreinforced cushion. The aging behavior of the two geogrids reduces the load bearing capacity of the reinforced cushion by influencing the property of the interface between the geogrid and sand.